Characterization of High-Temperature Proton-Exchange Membranes Based on Phosphotungstic Acid Functionalized Mesoporous Silica Nanocomposites for Fuel Cells - Zeng, J.; Jiang, San Ping (American Chemical Society, 2011)
The synthesis and characteristics of high-temperature proton-exchange membranes based on mesoporous silica nanocomposite functionalized with phosphotungstic acid (HPW) were investigated in detail for applications in protonexchange membrane fuel cells (PEMFCs) and direct methanol fuel cells (DMFCs). The HPWmeso-silica nanocomposites were characterized by small-angle X-ray scattering (SAXS), FTIR spectroscopy, Raman spectroscopy, TGA, N2 absorption isotherm, water uptake, TEM, conductivity, and fuel cell performance. The spectroscopy results indicate interactions between the Keggin anions of HPW and meso-silica and the possible formation of (SiOH2)(H2PW12O40 species. The results show that the proton conductivity of the HPWmesosilica nanocomposites depends strongly on the content ofHPW. The threshold for the proton conductivity of the nanocomposite is 10 wt %. The best proton conductivity is 0.07 S cm1 at 25 C under 100% relative humidity (RH) with an activation energy of ~14 kJ mol1, obtained on HPWmeso-silica nanocomposites with 6783% HPW. A PEMFC based on a HPWmeso-silica membrane produced a power output of 308 mW cm2 at 80 C and 80% RH in H2/O2, 206 mW cm2 at 80 C and 80% RH in H2/air, and 134 mW cm2 at 160 C in methanol/air without external humidification. The high tolerance of HPWmeso-silica nanocomposites toward RH fluctuations demonstrates the unique high water retention capability of HPWmeso-silica nanocomposites. The results indicate that HPWmeso-silica forms a promising proton-exchange membrane for PEMFCs and DMFCs operating at high temperatures.